Meningkatkan Aktivitas Dan Hasil Belajar IPA Menggunakan Model PJBL, SAVI, & NHT Pada Siswa Kelas V SD - Iqlima Rahmatunnisa Hefny; Tika Puspita Widya Rini (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study is the low activity and learning outcomes of students in the science content of class V SDN Belitung Utara 3 Banjarmasin, this is because the learning is still teacher-centered, the lack of student activity in the learning process, and the learning model is less varied so students get bored. Through the Project Based Learning model, SAVI (Somatic, Auditory, Visual, Intellectual), and Numbered Head Together this can be the best solution. This study uses Classroom Action Research (CAR). The purpose of this classroom action research is to prove an increase in teacher activity, student activity, and student learning outcomes. Collecting data on teacher and student activities was obtained by means of observation sheets while student learning outcomes were obtained through individual evaluation tests. The results of this study indicate that teacher activity achieves very good criteria at meeting 4. Students' classical activity reaches 95% with very active criteria at meeting 4. Student learning outcomes achieve 95% classically at meeting 4. Based on these findings it can be concluded that the use of the Project Based model Learning, SAVI (Somatic, Auditory, Visual, Intellectual) and Numbered Head Together can increase student learning activities and results in science content.